Improving Energy Efficiency with Reusage Outlet Stream of Heat Exchanger for Formaldehyde Production from Methanol - Iftinan, Hasna Naila; Andari, Chalista Nadhira; Khotimah, Dinda Khusnul; Husna, Hanum Iffah (Journal of Chemical Engineering Research Progress, 2025)
Formaldehyde is one of the chemical products that has an important role in various industries with the percentage of global production consistently increasing over the past ten years. However, the production of formaldehyde requires considerable energy consumption. The purpose of this study is to examine other alternatives to improve energy efficiency in the formaldehyde production process. This study focuses on the reutilization of heat generated from the heat exchanger to minimize the net energy generated. The process modification was simulated using Aspen HYSYS and the net energy comparison between the original and modified process was calculated using the net-energy formula. The results show that the Net-Energy (NE) value for the original process is 18,839,836 kJ/h while for the modified process it is 4,123,000 kJ/h. This result shows that the modified process is efficient to reduce Net-Energy and can increase energy efficiency in the formaldehyde production process through the methanol dehydrogenase process. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).